LEÓN ASSEMBLIES C.1188 AND COUNCIL AS A BASIS FOR SOCIAL STRUCTURE AND CIVIC PARTICIPATION. - Melo Carrasco, Diego; Gordo Molina, Ángel (Revista de Historia Social y de las Mentalidades, 2016)
1118 was the year when it was first officially  recorded the attendance of elected men from  each city to the royal assembly, along with the  traditional groups which regularly participated  in Leonese politics, which was since then  conducted by Alfonso Ix. In regard to this  historic landmark, we ask whether that record  was indeed a reflection of those new men’s first  actual participation in such kind of meeting  called upon by the Leonese sovereign or,  rather it was only the first time their attendance was documented, and they had already been  participating in the on-going relationships  between the crown and the rural communities.  Analyzing the relationship between the king and  the councils through the fuero, and examining  the social bases that led to the peasant social  organization, we were able to determine that  elected council representatives had been referred  to in a number of documents before and after  Alfonso IX’s assembly. This finding suggests that  the social base of the decision-making process  had been broadened, and that from now on  elected representatives became the main support  of the Leonese monarchy’s actions.
Keywords: Kingdom of León; Alfonso Ix of León; Representation; Rural societies; Regal assemblies